The burden and predictors of latent tuberculosis infection among elder adults in high epidemic rural area of tuberculosis in Zhejiang, China - Wang, Wei; Chen, Xinyi; Chen, Songhua; Zhang, Mingwu; Wang, Wei; Hao, Xiaogang; Liu, Kui; Zhang, Yu; Wu, Qian; Zhu, Ping; Chen, Bin (Frontiers in Cellular and Infection Microbiology, 2022)
Diagnosis and treatment of latent tuberculosis infection (LTBI) is critical to tuberculosis (TB) control. Identifying the risk factors associated with LTBI can contribute to developing an optimize strategy for LTBI management. We conducted a survey of adults aged 65 years and older living in rural areas in Zhejiang Province during July, 2021, followed by a one-year follow-up period to determine TB incidence. Participants underwent a physical examination and 5–6 mL of blood was drawn to test for Mycobacterium tuberculosis infection A total of 1856 individuals participated in the study, of whom 50.5% were males and 80.1% were married. Most participants (96.8%) often opened windows for ventilation at home. One-third (33.4%) of participants had abnormal chest radiographs and 34.9% had LTBI. Nine participants (0.5%) developed active TB patients during one-year follow-up period. People who frequented closed entertainment places such as chess and cards rooms had a relatively high percent of LTBI(39.5%). Factors associated with a higher risk of LTBI in multivariable logistic regression analysis included being male (odds ratio [OR]:1.32; 95% confidence interval [CI] =:1.01-1.72), smoking (OR: 1.43; 95% CI:1.04-1.97) and not opening windows for ventilation at home frequently (OR: 1.88; 95% CI: 1.10–3.22), and an abnormal chest radiographs (OR; 1.48; 95% CI; 1.20–1.81). LTBI was prevalent among the elder adults living in high epidemic rural area of TB in Zhejiang province. Men, people who smoking, people without the habit of ventilate at home should be targeted for LTBI screen to accelerate the decline of TB epidemic in Zhejiang Province.